2020
DOI: 10.1101/2020.11.27.400457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring stimulus-evoked neurophysiological differentiation in distinct populations of neurons in mouse visual cortex

Abstract: Despite significant progress in understanding neural coding, it remains unclear how the coordinated activity of large populations of neurons relates to what an observer actually perceives. Since neurophysiological differences must underlie differences among percepts, differentiation analysis—quantifying distinct patterns of neurophysiological activity—is an “inside out” approach that addresses this question. We used two-photon calcium imaging in mice to systematically survey stimulus-evoked neurophysiological … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…A recent calcium imaging study showed that the ND of cellular fluorescent responses was higher for naturalistic stimuli (movies of predators and prey) compared to phase-scrambled versions of the same movies in in layer 2/3 of two specific regions of the mouse brain, VISal and VISam. In layers 4 and 5 of the same areas and in all layers of the other areas studied (VISp, VISl, and VISpm), the difference was non-significant (Mayner et al, 2022). In contrast, activity in any recorded visual cortical layer and region could be used to accurately decode stimulus type (naturalistic vs. scrambled).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…A recent calcium imaging study showed that the ND of cellular fluorescent responses was higher for naturalistic stimuli (movies of predators and prey) compared to phase-scrambled versions of the same movies in in layer 2/3 of two specific regions of the mouse brain, VISal and VISam. In layers 4 and 5 of the same areas and in all layers of the other areas studied (VISp, VISl, and VISpm), the difference was non-significant (Mayner et al, 2022). In contrast, activity in any recorded visual cortical layer and region could be used to accurately decode stimulus type (naturalistic vs. scrambled).…”
Section: Introductionmentioning
confidence: 85%
“…Thus, the richness of perceptual experience ("meaningfulness of stimuli") should correspond to the richness of neural activity (and not the richness of the stimulus) in the specific neuronal populations that are the physical substrate of the perceptual experience. This richness of neural activity has been quantified in several recent studies by measuring how many different states the brain or a specific brain region enters during a period of time, called neurophysiological differentiation (ND) (Synek, 1988;Gosseries et al, 2011;Barttfeld et al, 2015;Boly et al, 2015;Hudetz et al, 2015;Solovey et al, 2015;Mayner et al, 2022).…”
Section: Introductionmentioning
confidence: 99%